Reactions of β‐Azolylenamines with Sulfonyl Azides as an Approach to N‐Unsubstituted 1, 2, 3‐Triazoles and Ethene‐1, 2‐diamines. Issue 17 (30th April 2014) - Efimov, Ilya; Bakulev, Vasiliy; Beliaev, Nikolai; Beryozkina, Tetyana; Knippschild, Uwe; Leban, Johann; Zhi‐Jin, Fan; Eltsov, Oleg; Slepukhin, Pavel; Ezhikova, Marina; Dehaen, Wim
Abstract: The reactions of β‐azolylenamines1 with sulfonyl azides2 in acetonitrile furnished 1 H ‐4‐(azol‐5‐yl)‐1, 2, 3‐triazoles3 in yields of 52–93 %. β‐Benzoylenaminones and β‐nitroenamine of type1 also reacted with tosyl azide to form the same type of products3, proving the generality and efficiency of the method for the synthesis of N ‐unsubstituted 1, 2, 3‐triazoles. On the other hand, the reactions of 3‐(1‐aryl‐1, 2, 3‐triazol‐5‐yl)enamines with tosyl azide in the absence of a solvent afforded a mixture of ( E )‐1‐dimethylamino‐2‐tosylaminoethenes5 and N, N ‐dimethyl‐ N′ ‐tosylformamidine6 in yields of 40–50 and 20 %, respectively. The formation of a variety of compounds from the reactions of enamines1 with sulfonyl azides2 is rationalized by the various possible transformations of the intermediate 5‐dimethylamino‐1, 2, 3‐triazolines7 . Abstract : This paper deals with reactions of β‐azolylenamines with sulfonyl azides. Variation of the reaction conditions leads to different products